Low-field-actuated giant magnetocaloric effect and excellent mechanical properties in a NiMn-based multiferroic alloy. (March 2018) - Cong, D.Y.; Huang, L.; Hardy, V.; Bourgault, D.; Sun, X.M.; Nie, Z.H.; Wang, M.G.; Ren, Y.; Entel, P.; Wang, Y.D.
Abstract: Multiferroic magnetic shape memory alloys with first-order magntostructural transformation exhibit much enhanced magnetocaloric effect which incorporates the latent heat associated with the phase transformation itself, but they suffer from the drawbacks of large hysteresis and transformation interval and consequently too high critical field to actuate the magnetocaloric effect, greatly impeding their applications. Here, by generating a kind of specific stacking-mediated structure of martensite through minor Al substitution to improve the geometric compatibility between martensite and austenite in the Ni40 Co10 Mn40 Sn9 Al1 alloy, we greatly reduced the thermal hysteresis and transformation temperature interval while conserving the large magnetization difference between the two phases. Consequently, a low-field-actuated giant magnetocaloric effect with isothermal entropy change of 23 J kg −1 K −1 for a field change from 0 to 2 T, which is among the highest values reported heretofore for all magnetocaloric materials, was successfully achieved. Meanwhile, with minor Al substitution, the present single-phase multiferroic alloy that is intermetallic in nature exhibits superior mechanical properties, including excellent compressive properties over a wide temperature range and a relatively high fracture toughness, which are quite beneficial for practical applications. Incorporating the advantages of low cost, environment friendliness and easy fabrication, this alloy shows great potential for magnetocaloric applications. Graphical abstract: Image 1